Factors Associated with Economic Growth: An Investigation on the Government Spending in R&D. - Trần, Nhật Thiện (World Scientific Publishing Co. Pte. Ltd., 2022)
This chapter aims to study the impact of R&D programs on economic growth. The long-run growth rate is fueled by R&D investment, and the government levies taxes on labor income and capital returns to finance this investment. The research investigates the interplay between R&D activity and the effects of tax policies. In particular, this study shows that a rise in R&D investment enhances the efficiency of unskilled labor so that income inequality between unskilled and skilled workers can be reduced, consequently increasing economic growth.